Variations in stress and driving pore fluid pressure ratio using vein orientations along megasplay faults : Example from the Nobeoka Thrust, Southwest Japan. (19th August 2016) - Otsubo, Makoto; Miyakawa, Ayumu; Kawasaki, Ryoji; Sato, Katsushi; Yamaguchi, Asuka; Kimura, Gaku
Abstract: The Nobeoka Thrust of Southwest Japan is an on‐land example of an ancient megasplay fault that provides an excellent record of deformation and fluid flow at seismogenic depths. The present study reports: (i) temporal stress changes for the seismogenic period of the Nobeoka Thrust; and (ii) spatial heterogeneities in driving pressure ratios P* obtained from mineral veins around the Nobeoka Thrust fault zone. Many quartz veins that filled mode I cracks can be observed in the hanging wall and footwall of the thrust. Inversion for stress orientation suggests that normal faulting dominated in both the hanging wall and footwall, with similar stress axis orientations in both. The orientation of σ3 for the estimated stress regime is parallel to the slip direction of the Nobeoka Thrust. The detected normal‐faulting‐type stress regimes likely resulted from post‐seismic stress buildup after megathrust earthquakes. The hanging wall of the Nobeoka Thrust has smaller P* values than the footwall. Two possible explanations are proposed for the observed spatial variations in the driving pore fluid pressure ratio, P*: spatial variations in pore fluid pressure Pf are directly responsible for P* variations, or P* variations are controlled by differences in mechanical properties between the hanging wall and footwall. Abstract : Many quartz veins that filled mode I cracks are present in the hanging wall and footwall of the Nobeoka Thrust. The normal‐faulting‐type stress regimes estimated from the veins likely resulted from postseismic stress buildup after megathrust earthquakes. The observed spatial variations in driving pressure ratios indicate that spatial variations in pore fluid pressure or differences in mechanical properties between the hanging wall and footwall.